THE EFFECT OF CROSSFIT ON HEART FUNCTION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Comprehensive physical fitness of Cadet Girls, health improvement, general endurance and fast-strength quality training, mastering the basics of running the competition in a combination way, developing special endurance, gaining competition experience.